Does Amifostine Reduce Metabolic Rate? Effect of the Drug on Gas Exchange and Acute Ventilatory Hypoxic Response in Humans - Jaideep J. Pandit; Caroline Allen; Evelyn Little; Federico Formenti; Adrian L. Harris; Peter A. Robbins (MDPI AG, 2015)
Amifostine is added to chemoradiation regimens in the treatment of many cancers on the basis that, by reducing the metabolic rate, it protects normal cells from toxic effects of therapy. We tested this hypothesis by measuring the metabolic rate (by gas exchange) over 255 min in 6 healthy subjects, at two doses (500 mg and 1000 mg) of amifostine infused over 15 min at the start of the protocol. We also assessed the ventilatory response to six 1 min exposures to isocapnic hypoxia mid-protocol. There was no change in metabolic rate with amifostine as measured by oxygen uptake (p = 0.113). However in carbon dioxide output and respiratory quotient, we detected a small decline over time in control and drug protocols, consistent with a gradual change from carbohydrate to fat metabolism over the course of the relatively long study protocol. A novel result was that amifostine (1000 mg) increased the mean ± SD acute hypoxic ventilatory response from 12.4 ± 5.1 L/min to 20.3 ± 11.9 L/min (p = 0.045). In conclusion, any cellular protective effects of amifostine are unlikely due to metabolic effects. The stimulatory effect on hypoxic ventilatory responses may be due to increased levels of hypoxia inducible factor, either peripherally in the carotid body, or centrally in the brain.